Penerapan Kawat Litz Pada Motor BLDC Untuk Peningkatan Gaya Dorong Per Daya - Muhammad Syauqi Firdausi; Tri Wahyu Supardi; Roghib Muhammad Hujja (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2023)
Copper loss can cause a decrease in performance in BLDC motors, so efforts will be made to reduce copper loss by using Litz wire. Additionally, there have been studies that simulate the performance of Litz wire, but they have not been directly applied, especially to propeller thrust. The objective of this research is to implement Litz wire in a BLDC motor and analyze its performance for an increase in propeller thrust per power. The BLDC motor is wound with single wire and Litz wire. The analysis conducted compares the resistance, copper loss, thrust force, and thrust-to-power ratio of the single wire and Litz wire with the same wire cross-sectional area. The BLDC motor is equipped with a propeller to measure the thrust force. The average resistance of the single wire is 0.43 Ohms, while the Litz wire is 0.38 Ohms. The copper loss of the Litz wire is 7% lower than a single wire. The Litz wire exhibits a 3% improvement in thrust force compared to the single wire in the testing. The thrust-to-power ratio of the Litz wire is also 3% better during the testing.